P 111 Clinical trials in neurological disorders causing vertigo. Issue 10 (October 2017) - Naumann, I.; Goldschagg, N.; Muth, C.; Teufel, J.; Strupp, M.; Bayer, O.
Abstract : The German Center for Vertigo and Balance Disorders (DSGZ) is an interdisciplinary center for research and treatment of vertigo, balance and ocular motor disorders. The long-term aim is to establish a patient-oriented research institution that is networked with all involved disciplines and methods. This includes also the establishment of a study infrastructure for prospective multicenter clinical trials. With this abstract we would like to give an overview over the current clinical trials conducted in collaborations with other investigational sites throughout Germany. During the last 20 years vestibular migraine has been identified as a distinct type of migraine with the leading symptom of vertigo. These attacks lasting minutes to hours, have considerable impact on quality of life, and can result in economical and social losses. The trial drug metoprolol with proven efficacy in migraine prevention is commonly used in the treatment of vestibular migraine. So far its indication in vestibular migraine is only based on expert opinion. The aim of thePROVEMIG study (a double-blind, placebo-controlled trial) is to demonstrate the superiority of metoprolol succinate treatment regarding the number of vertigo attacks and the number of headache attacks per month compared to placebo in patients with vestibular migraine. The leading symptom of vestibular paroxysmia (VP) are spontaneous recurrent attacks of rotatory or postural vertigo lasting seconds to a few minutes sometimes with accompanying symptoms like tinnitus or hypoacusis. The high frequency as well as the unpredictability of these vertigo attacks result in strong impact on quality of life. Based on the pathophysiological concept of neurovascular compression as for trigeminus neuralgia the sodium channel blocker Carbamazepin (CBZ) is used as off-label therapy for patients with VP. The purpose of theVesPa study is to demonstrate within a controlled clinical trial that CBZ is efficacious in reducing the frequency, duration and severity of vertigo attacks, the number of vertigo per month and improving quality of life in patients with VP. Benign peripheral paroxysmal positional vertigo (BPPV) is characterized by short but intense attacks of rotatory vertigo induced by changes in the position of the head or body, accompanied oscillopsia, nausea and vomiting. Furthermore, nearly 50 percent of these patients also experience a relapse of BPPV. Retrospective studies revealed that patients with BPPV show decreased vitamin D levels. The goal of theVitD@BPPV study is to investigate the efficacy of vitamin D in reducing the amount of patients with one or more recurrences of BPPV. Interested study sites are welcome to contact the clinical study center of the DSGZ athttp://ifb.klinikum.uni-muenchen.de/de/Studienzentrum orIFB-Studienzentrale@med.uni-muenchen.de .